Promoter Mutations That Increase Amyloid Precursor-Protein Expression Are Associated with Alzheimer Disease - Theuns, Jessie (The American Society of Human Genetics, 2006)
Genetic variations in promoter sequences that alter gene expression play a prominent role in increasing susceptibility to complex diseases. Also, expression levels of APP are essentially regulated by its core promoter and 5′ upstream regulatory region and correlate with amyloid β levels in Alzheimer disease (AD) brains. Here, we systematically sequenced the proximal promoter (−766/+204) and two functional distal regions (−2634/−2159 and −2096/−1563) of APP in two independent AD series with onset ages ⩽70 years (Belgian sample, n=180; Dutch sample, n=111) and identified eight novel sequence variants. Three mutations (−118C→A, −369C→G, and −534G→A) identified only in patients with AD showed, in vitro, a nearly twofold neuron-specific increase in APP transcriptional activity, similar to what is expected from triplication of APP in Down syndrome. These mutations either abolished (AP-2 and HES-1) or created (Oct1) transcription-factor binding sites involved in the development and differentiation of neuronal systems. Also, two of these clustered in the 200-bp region (−540/−340) of the APP promoter that showed the highest degree of species conservation. The present study provides evidence that APP-promoter mutations that significantly increase APP expression levels are associated with AD.